The radial artery is protective in women and men following coronary artery bypass grafting—a substudy of the radial artery patency study - Tam, Derrick Y.; Deb, Saswata; Nguyen, Bao; Ko, Dennis T.; Karkhanis, Reena; Moussa, Fuad; Fremes, Jaclyn; Cohen, Eric A.; Radhakrishnan, Sam; Fremes, Stephen E.; Radial Artery Patency Study Investigators, on behalf of the (Annals of Cardiothoracic Surgery; Vol 7, No 4 (July 31, 2018): Coronary Revascularisation—Cardiology for the Surgeon, 2018)
Background: Studies have demonstrated that female sex is an adverse risk factor in CABG. The primary aim of this study was to determine whether the radial artery (RA) was associated with reduced angiographic occlusion compared to the saphenous vein graft (SVG) stratified by sex in the multi-centered Radial Artery Patency Study (NCT00187356). Methods: Between 1996–2001, 529 patients less than 80 years, with graftable triple-vessel disease underwent isolated CABG across 11 centers with late angiographic and clinical follow-up. The primary objective was to compare complete occlusion of RA and SVG with respect to sex. The secondary objective was to determine cumulative patency of both grafts along with predictors of late graft occlusion stratified by sex. The additional objective was to compare major adverse cardiac events (MACE, defined as cardiac mortality, myocardial infarction or re-intervention) between women and men. Results: Of the 529 enrolled patients (13.4% women), 269 (women: n=41, 15.2%) underwent late angiography at a mean of 7.7±1.5 years after CABG. Women were older (64.1±6.7 versus 59.1±8.0 years, P